Advertisement call of Scinax camposseabrai (Bokermann, 1968) (Anura: Hylidae), with comments on the call of three species of the Scinax ruber clade - Novaes, Gabriel; Zina, Juliana (Zootaxa, 2016)
Scinax camposseabrai was allocated into the Scinax ruber clade by Caramaschi & Cardoso (2006) by overall similarities as snout not pointed, breeding in open areas, and an advertisement calls with multipulsed notes. This assumption about the call was based solely on an onomatopoeia provided by Bokermann (1968). Herein we provide a formal description of the advertisement call of S. camposseabrai and compare it with described calls of other S. ruber clade species. Additionally, we provide descriptions of the advertisement calls of three sympatric species of the S. ruber clade: S. eurydice (Bokermann), S. pachycrus (Miranda-Ribeiro) and S. cf. x-signatus.